Fruit set, weight, and symmetry of cherimoya fruits (Annona cherimola Mill.) from flowers manually pollinated with insufflator and paint brush - Apolinario , Jorge (2025)
Low yields of cherimoya (Annona cherimola Mill.) are mainly attributed to poor natural pollination of its flowers, so manual pollination is the most important alternative. The present research aimed to determine the effectiveness of manual pollination in increasing fruit set, weight, and symmetry of the cherimoya Cumbe ecotype, pollinating four times between 6:00 a.m. and 4:00 p.m. of the two days of its flower opening cycle and using the paint brush and insufflator methods, under conditions of the Huaura Valley, Peru. The highest fruit set (71.9 % - 85.0 %) was achieved with all pollinations on day 1 and those carried out until 10:00 a.m. on day 2; and the lowest (31.3 % - 40.2 %) occurred with pollinations on day 2 from 12:00 p.m. to 1:00 p.m. Fruit set was zero in the control with natural pollination and when pollinated on day 2 from 3:00 p.m. to 4:00 p.m. No differences were found in fruit set between the paint brush and insufflator methods at any application time on either flower opening day. The highest fruit weight (437.6 g - 675.1 g) and the best symmetry (degree of deformation between 1.4 and 1.8) were obtained by pollinating on day 1 until 1:00 p.m., and day 2 until 10:00 a.m. The lowest weight (134.5 g - 251.9 g) and the lowest symmetry (degree of deformation between 2.1 and 2.7) resulted from pollinations on day 1 from 3:00 to 4:00 p.m., and on day 2 from 12:00 p.m. to 1:00 p.m. As with fruit set, no differences were found in the weight and shape of the fruits between the two manual pollination methods at any time.